IMPLIKASI PENGELOLAAN KELAS DALAM PEMBELAJARAN PAI UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS II DI MI ROUDHOTUL QUR’AN AZZAM SAKO KABUPATEN BANYUASIN - Leo Saputra; Meiryani; Afiantri Ni’matun Nisa; Ami Latifah (UNISAN JURNAL, 2023)
This examination plans to portray the ramifications of homeroom the executives in PAI learning on expanding interest in learning for class II understudies at MI Roudhotul Qur'an Azzam Sako, Banyuasin Regime. This kind of exploration utilizes clear subjective. Information assortment was done by perception, meetings and documentation. Information investigation methods use information decrease, information show, and information check. To test the legitimacy of the information, a validity test was utilized which was demonstrated by triangulation. The exploration results show that there are a few parts of study hall the executives, specifically parts of learning approaches and standards. Homeroom the board approaches include: a power approach by furnishing them with learning at school, which can appear as checking understudy conduct. Move toward dangers with expanded discipline. The solution approach in overseeing learning becomes agreeable and pleasant for understudies. Showing Approach by applying showing strategies in homeroom the board. The conduct change approach focuses on understudies, gets some information about their hardships and some of the time tackles the issues they face. Socio-Close to home Methodology by focusing on understudies. Bunch way to deal with make it simpler to finish tasks. The flexible methodology picks the right exercises in class, picking exercises in light of the material. The standards of homeroom the board that educators should apply are excited, testing, shifted with different learning techniques and systems. Adaptability in planning an open to growing experience. Accentuation on sure things and imparting self-control